Genetic diversity of infective larvae of Gnathostoma spinigerum (Nematoda: Gnathostomatidae) in freshwater swamp eels from Thailand - P. Eamsobhana (2018)
© Cambridge University Press 2016. Human gnathostomiasis is a food-borne zoonosis caused by a tissue nematode of the genus Gnathostoma. The disease is highly endemic in Asia, including Thailand. The freshwater swamp eel (Monopterus albus), the second intermediate host of the gnathostome nematode, has an important role in transmitting the infection in Thailand. Surveys on the infective larvae of Gnathostoma spinigerum based on morphological features in freshwater swamp eels have been performed continuously and reported in Thailand. However, there is still limited molecular data on intra-species variations of the parasite. In this study, a total of 19 third-stage larvae of morphologically identified G. spinigerum were collected from 437 liver samples of freshwater swamp eels purchased from a large wholesale market in Bangkok, Thailand. Molecular characterization based on mitochondrial cytochrome c oxidase subunit I (COI) sequences was performed to elucidate their genetic variations and phylogenetic relationship. Among the 19 infective larvae recovered from these eels, 16 were sequenced successfully. Phylogenetic analyses inferred from the partial COI gene showed the presence of three distinct COI haplotypes. Our findings confirm the presence of G. spinigerum as the main species in Thailand.